2015
DOI: 10.1007/s10482-015-0479-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the cell division-related ssg genes in Streptomyces coelicolor reveals direct control of ssgR by AtrA

Abstract: SsgA-like proteins are a family of actinomycete-specific regulatory proteins that control cell division and spore maturation in streptomycetes. SsgA and SsgB together activate sporulation-specific cell division by controlling the localization of FtsZ. Here we report the identification of novel regulators that control the transcription of the ssgA-like genes. Transcriptional regulators controlling ssg gene expression were identified using a DNA-affinity capture assay. Supporting transcriptional and DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…There is also growing evidence that besides DasR, the TetR6family regulator AtrA plays a role in carbon utilization ( (Fig. 4) 206 , the transcriptional activator of the gene encoding SsgA, which is involved in cell division and sporulation 207,208 Interestingly, there is an intricate link between Rok7B7, DasR and CCR, which in turn has important implications for the control of antibiotic production. Proteomic comparison of S. coelicolor and a glkA null mutant showed that glucose activates the expression of Rok7B7 in a Glk6independent manner 214 , which was later confirmed by transcriptomic analysis 215 .…”
Section: Competition Between Atra Rok7b7 and Dasr And Connections Tomentioning
confidence: 99%
See 1 more Smart Citation
“…There is also growing evidence that besides DasR, the TetR6family regulator AtrA plays a role in carbon utilization ( (Fig. 4) 206 , the transcriptional activator of the gene encoding SsgA, which is involved in cell division and sporulation 207,208 Interestingly, there is an intricate link between Rok7B7, DasR and CCR, which in turn has important implications for the control of antibiotic production. Proteomic comparison of S. coelicolor and a glkA null mutant showed that glucose activates the expression of Rok7B7 in a Glk6independent manner 214 , which was later confirmed by transcriptomic analysis 215 .…”
Section: Competition Between Atra Rok7b7 and Dasr And Connections Tomentioning
confidence: 99%
“…. Disruption of atrA suggests it activates transcription of ssgR206 , and direct binding of AtrA within the upstream regulatory region of ssgR was confirmed by ChIP6seq (McDowall et al, unpubl. data).The ROK6family protein, Rok7B7 takes up an interesting position in the regulatory network as it connects the control of antibiotic production and carbon catabolite repression209 .…”
mentioning
confidence: 93%
“…Previous work revealed that the small protein SCO1839 is a candidate nucleoid-associated protein (NAP) (19), and it specifically binds to the promoter region of the sporulation regulatory gene ssgR (22). SsgR activates transcription of ssgA , which encodes a pleiotropic developmental regulator and activator of sporulation-specific cell division in streptomycetes.…”
Section: Resultsmentioning
confidence: 99%
“…Like DasR, the TetR‐family transcriptional regulator AtrA is highly conserved in streptomycetes, and AtrA is required for actinorhodin production in S. coelicolor and streptomycin production in Streptomyces griseus , by directly controlling the pathway‐specific activator genes actII ‐ORF4 and strR , respectively (Uguru et al ., ; Hong et al ., ). AtrA affects multiple regulatory pathways, including those that control sporulation (Nothaft et al ., ; Kim et al ., ). Interestingly, AtrA controls both the initial and final steps of the proposed DasR‐mediated signalling pathway, namely the internalization of the signal (GlcNAc) via the activation of the transporter gene nagE2 , and activation of the biosynthetic cluster for actinorhodin production via the transcriptional activation of actII‐ORF4 (Nothaft et al ., ).…”
Section: Cross‐talk Between Atra Dasr and Rok7b7mentioning
confidence: 97%